Hubungan antara kelelahan, motivasi belajar, dan aktivitas fisik terhadap tingkat prestasi akademik - Welong, Seftian Surya; Manampiring, Aaltje Ellen; Posangi, Jimmy (Jurnal Biomedik : JBM, 2020)
Abstract: This study aim to determine between fatigue, learning motivation, and physical activity on the level of academic achievement use quantitative study. The population is all students of the specialization Ocupational Health and Safety class of 2017 totaling 60 Students and the sample is the total population. Statistical analysis the chi square test. The results of the study level of academic achievement found category good 60%, very good 40%. Fatigue found category not found 58.3%, tired of 41.7%. Motivation to learn found low category 51.7%, high of 48.3%. Physical activity found categories quite 53.3%, less 46.7%. The results of the chi square test confirms there is a relationship between fatigue on the level of academic achievement. The results of the chi square test confirms there is a relationship between learning motivation on the level of academic achievement. The results of the chi square test confirms there is a relationship between physical activity on the level of academic achievement. There is a relationship between fatigue, motivation to learn, and physical activity on the level of academic achievement.Keywords: achievement, fatigue, motivation, physical activity Abstrak: Penelitian ini untuk mengetahui hubungan antara kelelahan, motivasi belajar, aktivitas fisik terhadap tingkat prestasi akademik. Jenis penelitian kuantitatif. Populasi ialah seluruh mahasiswa peminatan Kesehatan dan Keselamatan Kerja Angkatan 2017 berjumlah 60 Mahasiswa dan sampel adalah total populasi. Analisis statistik uji chi square. Hasil penelitian tingkat prestasi akademik ditemukan kategori baik 60%, sangat baik 40%. Kelelahan ditemukan kategori tidak lelah 58.3%, lelah 41.7%. Motivasi belajar ditemukan kategori rendah 51.7%, tinggi 48,3%. Aktivitas fisik ditemukan kategori cukup 53.3%, kurang 46.7%. Hasil uji chi square menegaskan ada hubungan antara kelelahan terhadap tingkat prestasi akademik. Hasil uji chi square menegaskan ada hubungan antara motivasi belajar terhadap tingkat prestasi akademik. Hasil uji chi square menegaskan ada hubungan antara aktivitas fisik terhadap tingkat prestasi akademik. Terdapat hubungan antara kelelahan, motivasi belajar, dan aktivitas fisik terhadap tingkat prestasi akademik.Kata kunci: prestasi, kelelahan, motivasi, aktivitas fisik